A study of genre changes and privileged pedagogic identity in teaching contest discourse - Liu, Ning (2017)
There are various types of educational contests held across disciplines and institutions in China every year, including debate contests, speech contests, reading contests, writing contests, spoken English contests, and teaching contests. The Shanghai Foreign Language Education Press National College English Teaching Contest (hereafter SFLEP contest) is such an example. It is a large-scale teaching contest held annually throughout 1,500 Chinese universities for Chinese EFL teachers engaged in tertiary education. Every year, 20 winning contestant teachers are chosen from the contest and their mock teachings (a particular contest segment in which the contestant teachers teach in a quasi-classroom environment) in the finals of the SFLEP contest are recorded and presented to the public through various media, such as Youku (a very popular online video website in China, www.youku.com). Moreover, the contest adjudicators make comments on these privileged examples and their comments are published by one of the contest sponsors, the Shanghai Foreign Language Education Press, as well. As these mock teachings are not authentic classroom teaching, but the teaching performances in the contest, they represent the privileged meta-pedagogical examples that the contest organizers want to present to the contest audience. For the same reason, these comments of the mock teachings also represent the meta-pedagogical opinions of the contest adjudicators in the contest, which the contest organizers want the contest audience to access. There are studies which explore the collective identity types reflected in the contest discourses and studies which discuss the impact of teaching contest on authentic teaching. The former type of study offers ways of understanding teaching contest practices as spontaneous events which put forward their particular meta-pedagogical models to the contest audience; the second type of study offers ways of understanding the impact and washback influences of these models on authentic teachings. No prior studies, however, explore how the teaching practices in authentic teachings are borrowed into the teaching contest. It is the hypothesis of the present thesis that the classroom-based pedagogic models are borrowed in and adapted in the contest discourses before they are presented to the contest viewers. The research purpose of the thesis is to test this hypothesis with discourse analytic approaches. The data used in the thesis include the published recordings of 20 winning mock teachings in the finals of 2nd SFLEP contest, together with 40 published adjudicators’ comments on these mock teachings. The analytic approach used in the thesis is primarily Martinian systemic functional linguistics (e.g. Martin, 2004). The thesis goes through a three-step analysis of the data. Firstly, it analyzes the register configuration of the mock teaching discourse; secondly, it compares these analytic results with a prior study of ESL pedagogic genre (Lee, 2011); thirdly, it analyzes the contest adjudicators’ post-contest comments as to what genre instances and individuations are valued / devalued in these comments. The research results are three-fold. First, the research reports the particular register features of the mock teaching data used. Second, the mock teaching discourse as a genre is no different from the ESL pedagogic genre at its stages; however, it is different from the ESL pedagogic genre at its sub-stages, phases, and register configurations. Third, certain stages, sub-stages, and phases of the mock teaching genre are chosen and further evaluated by the contest adjudicators in their post-contest comments. Within these evaluated segments of the genre, instances are either valued or devalued. Moreover, the valued genre instances all point to Interventionism, a certain pedagogic type according to Bernsteinian pedagogical classification (see also Chapter 2). The research results lead to this thesis’ primary contribution by giving a new dimension for the explanation of the teaching contest discourse. Based on its research results, the thesis proposes that the teaching contest discourse as a macrogenre has the social function of borrowing in and changing the classroom pedagogic genre and then refining this genre for the purpose of representing a privileged meta-pedagogic identity in the contest. Apart from this, the thesis also makes contributions to SFL genre theories. First, it proposes that the genre changes in the mock teaching discourse are a phenomenon of genre blurring, as they maintain the abstract form of pedagogic genre while adapt this genre to the contest environment at more constitutional levels. Although prior SFL genre theories can define the mock teaching genre as a genre generated from pedagogic genre, there are no explanations of how the genre changes happen along with the register shift and ideological control. Second, it proposes that the evaluation of genre instances and individuations in the contest adjudicators’ post-contest comments is a phenomenon of genre solidification as the evaluation re-classifies a genre and picks certain instances to represent a privileged narrowed-down genre form in the contest. It is therefore a more delicate way to classify and solidify genre types.